Penglibatan wanita Melayu sebagai wakil rakyat dewan undangan negeri, 1999-2008 - Hanafi Fatimi, Abdul Rahman Zulkanain, Mohd Noor Arba'iyah (Universiti Pendidikan Sultan Idris, 2018)
Penglibatan wanita Melayu sebagai wakil rakyat dewan undangan negeri, 1999-2008 by Hanafi Fatimi, Abdul Rahman Zulkanain, Mohd Noor Arba'iyah,